Managing Conflicts with Wildlife: Living with Wild Hogs - William M. Giuliano; Holly K. Ober; Lauren Watine; Raoul Boughton; Don Coyner (EDIS, 2015)
Wild hogs are a popular species, pursued and hunted by many throughout Florida. They are also an important food source for the endangered Florida panther. But there are situations where they can become dangerous or damaging. In this 4-page fact sheet, we present some facts about hogs, describe dangers and problems they may cause, and provide suggestions on how to cope with these issues. Written by William M. Giuliano, Holly K. Ober, Lauren Watine, Raoul Boughton, and Don Coyner, and published by the UF Department of Wildlife Ecology and Conservation, December 2014. (Photo: M.S. Smith)